Inductors
The inductor design with a mixed particle core and conductive resin with varying particle sizes, along with a plating layer, addresses the issues of weak adhesion and high resistance in existing conductive pastes, enhancing fixing strength and reducing resistance.
Patent Information
- Application Number
- JP2021058572
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-03-30
AI Technical Summary
The use of conductive pastes with small average particle sizes for forming inductor external electrodes results in reduced contact area and increased resistance, while using acrylic resin to improve dispersibility leads to weak adhesion, causing the electrodes to peel off easily.
An inductor design with a core containing a mixture of large and small metal magnetic particles and a specific resin composition, combined with a conductive resin containing first and second conductive particles of different sizes, and a plating layer extending from the base electrode, enhances the fixing strength and reduces resistance.
The design improves the adhesion strength of external electrodes, reduces resistance, and prevents peeling, while maintaining a smooth surface without unevenness.
Smart Images

Figure 0007621157000003 
Figure 0007621157000004 
Figure 0007621157000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an inductor. [Background technology]
[0002] Patent Document 1 discloses a conductive paste for forming terminal electrodes of a multilayer ceramic electronic component. Patent Document 1 also discloses that the conductive paste contains a conductive powder and a resin component, the conductive powder is silver powder, and the average particle size is 0.1 μm or more and 10 μm or less. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2020-088353 Summary of the Invention [Problem to be solved by the invention]
[0004] When the conductive paste disclosed in Patent Document 1 is applied to the body of an inductor, which is a type of electronic component, to form an external electrode of the inductor, the average particle size of the conductive powder is relatively large, which reduces the contact area between the conductive particles and reduces the current path, resulting in a relatively high resistance value of the external electrode.
[0005] Therefore, the problem of the resistance value of the external electrodes can be improved by mixing a conductive powder with a smaller average particle size into the conductive paste. However, mixing a conductive powder with a smaller average particle size reduces the dispersibility of the conductive powder in the resin, so it is necessary to improve the dispersibility of the conductive powder by using, for example, an acrylic resin as a resin component. However, when an acrylic resin or the like is used as the resin component, the adhesive strength of the conductive paste to the element body is weakened, causing the external electrodes to easily peel off.
[0006] An object of the present invention is to provide an inductor having an element body capable of improving the fixing strength of external electrodes. [Means for solving the problem]
[0007] One aspect of the present invention is an inductor having an element body having a top surface, a mounting surface, end surfaces and side surfaces, in which a coil conductor is embedded in a core containing metal magnetic powder and resin, and external electrodes formed on the surfaces of the element body, in which the element body has a proportion of the metal magnetic powder of 96.7 wt % or more and 97.4 wt % or less and a proportion of the resin of 2.6 wt % or more and 3.3 wt % or less based on the total weight of the metal magnetic powder and the resin, and the external electrodes are formed on the surface of the element body with a conductive resin containing first and second conductive particles having different average particle diameters and resin. and a plating layer formed on a surface of the base electrode, the surface of the body with which the base electrode is in contact has a metal area ratio, which is the ratio of the area of the metal magnetic powder to the total area of the metal magnetic powder and the resin, of 65% to 75%, the plating layer having an extension portion extending from the base electrode to the surface of the body at least on the mounting surface of the body, and the metal area ratio of the area of the surface of the body with which the extension portion of the plating layer is in contact is higher than the metal area ratio of the area other than the area with which the external electrode is in contact. It has become The surface of the element body with which the extending portion of the plating layer is in contact has a metal area ratio of 65% to 75% and a surface roughness of 5.2 μm to 14.5 μm. . Effect of the Invention
[0008] According to the present invention, the fixing strength of the external electrodes can be improved. [Brief description of the drawings]
[0009] [Figure 1] 1 is a perspective view of an inductor according to a first embodiment of the present invention, viewed from the top side. [Diagram 2] FIG. 2 is a perspective view of the inductor as viewed from the mounting surface side. [Diagram 3] FIG. 2 is a transparent perspective view showing the internal configuration of an inductor. [Figure 4]1 is a schematic diagram of a manufacturing process of an inductor. [Diagram 5] 1 is a schematic diagram showing the configuration of an LT cross section of an inductor. [Figure 6] FIG. 11 is a diagram showing the relationship between surface roughness and adhesive strength of external electrodes. [Figure 7] FIG. 4 is a diagram showing the relationship between metal area ratio and surface roughness. [Figure 8] 13 is a diagram showing a micrograph of a cross section of an external electrode portion of an inductor together with a micrograph of the surface of the electrode formation portion. FIG. [Figure 9] 10 is a schematic diagram showing the configuration of an LT cross section of an inductor according to a second embodiment of the present invention. FIG. [Figure 10] 11 is a diagram showing the correspondence between the cross-sectional configuration of a portion including an extending portion of an external electrode and the planar configuration of an inductor as viewed from the mounting surface. FIG. [Figure 11] 11 is a schematic diagram showing the configuration of an LT cross section of an inductor according to a third embodiment of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. [First embodiment] FIG. 1 is a perspective view of an inductor 1 according to this embodiment as viewed from an upper surface 12 side, and FIG. 2 is a perspective view of the inductor 1 as viewed from a mounting surface 10 side. The inductor 1 of this embodiment is configured as a surface-mount electronic component and comprises a substantially rectangular body 2 and a pair of external electrodes 4 provided on the surface of the body 2, with one surface of the body 2 configured as a mounting surface 10 (FIG. 2) to be mounted on the surface of a circuit board (not shown).
[0011] Hereinafter, the surface of the element 2 facing the mounting surface 10 is defined as the top surface 12, and of the four surfaces other than the top surface 12 and the mounting surface 10, the surfaces at both ends of the element 2 in the longitudinal direction are referred to as end surfaces 14, and the remaining surfaces are referred to as side surfaces 16. 1, the distance from the mounting surface 10 to the top surface 12 is defined as the thickness T of the element body 2, the distance between a pair of side surfaces 16 is defined as the width W of the element body 2, and the distance between a pair of end surfaces 14 is defined as the length L of the element body 2. In addition, the direction of the thickness T is defined as the thickness direction DT, the direction of the width W is defined as the width direction DW, and the direction of the length distance is defined as the length direction DL.
[0012] FIG. 3 is a perspective view showing the internal configuration of the inductor 1. As shown in FIG. The element body 2 includes a coil conductor 20 and a core 30 having a substantially rectangular parallelepiped shape in which the coil conductor 20 is embedded, and is configured as a conductor-enclosed magnetic component in which the coil conductor 20 is enclosed in the core 30.
[0013] The core 30 is a molded body obtained by compression molding a mixture of magnetic metal powder (soft magnetic powder) and resin into a substantially rectangular parallelepiped shape by applying pressure and heat while the coil conductor 20 is contained therein.
[0014] In addition, the metal magnetic powder of this embodiment contains two types of particles: first magnetic particles having a relatively large average particle size, and second magnetic particles having a relatively small average particle size. As a result, during compression molding, the second magnetic particles, which are small particles, enter between the first magnetic particles having a relatively large average particle size together with the resin, thereby increasing the filling rate of the core 30 and also increasing the magnetic permeability. In this embodiment, the average particle sizes of the metal particles of the first magnetic particles and the second magnetic particles are 24.4 μm and 4.0 μm, respectively. The average particle size of the first magnetic particles is preferably 24 μm or more and 39 μm or less, and the average particle size of the second magnetic particles is preferably 3 μm or more and 5 μm or less. In addition, the metal magnetic powder may contain particles having an average particle size between the first magnetic particles and the second magnetic particles, thereby containing particles of three or more particle sizes.
[0015] In this embodiment, the first magnetic particles and the second magnetic particles are both particles having a metal particle and an insulating film covering the surface of the metal particle with a thickness of several nm to several tens of nm, the metal particle is made of Fe-Si amorphous alloy powder, and the insulating film is made of zinc phosphate. By covering the metal particle with the insulating film, the insulation resistance and the withstand voltage are increased. The amount of the second magnetic particles is 25% by weight based on the total weight of the magnetic particles contained in the mixed powder.
[0016] In addition, in the first magnetic particles, the metal particles may be Cr-less Fe-C-Si alloy powder, Fe-Ni-Al alloy powder, Fe-Cr-Al alloy powder, Fe-Si-Al alloy powder, Fe-Ni alloy powder, or Fe-Ni-Mo alloy powder.
[0017] In addition, in the first magnetic particles and the second magnetic particles, the insulating film may be made of other phosphates (magnesium phosphate, calcium phosphate, manganese phosphate, cadmium phosphate, etc.) or resin materials (silicone-based resins, epoxy-based resins, phenol-based resins, polyamide-based resins, polyimide-based resins, polyphenylene sulfide-based resins, etc.).
[0018] In the mixed powder of this embodiment, the resin material is an epoxy resin containing bisphenol A type epoxy resin as a main component. The epoxy resin may be a phenol novolac type epoxy resin. The resin material may be other than epoxy resin, and may be two or more types instead of one. For example, the resin material may be a thermosetting resin such as phenol resin, polyester resin, polyimide resin, polyolefin resin, etc., in addition to epoxy resin.
[0019] 3, the coil conductor 20 includes a winding portion 22 around which a conductor wire is wound, and a pair of lead-out portions 24 drawn out from the winding portion 22. The winding portion 22 is formed by winding the conductor wire in a spiral shape such that both ends of the conductor wire are located on the outer periphery and connected to each other on the inner periphery. Inside the element body 2, the coil conductor 20 is embedded in the core 30 with the central axis of the winding portion 22 aligned along the thickness direction DT of the element body 2, and the lead-out portions 24 are drawn out from the winding portion 22 to each of a pair of end faces 14 and electrically connected to the external electrodes 4.
[0020] The external electrode 4 is a so-called five-surface electrode that is provided over the entire surface of the end face 14, over a portion of the mounting surface 10 adjacent to the end face 14, the top surface 12, and a pair of side surfaces 16, and is electrically connected to the wiring of the circuit board by an appropriate mounting means such as solder.
[0021] The inductor 1 having such a configuration is used in a power supply circuit having a charge pump type DCDC converter that boosts voltage using a capacitor and a switch and an LC filter, and the power supply circuit is used in electronic devices such as personal computers, DVD players, digital cameras, TVs, mobile phones, smartphones, car electronics, medical and industrial machines, etc. However, the use of the inductor 1 is not limited to this, and it can also be used, for example, in tuning circuits, filter circuits, rectifying and smoothing circuits, etc.
[0022] In the inductor 1, an element protection layer may be formed on the entire surface of the element 2 excluding the area of the external electrodes 4. The material for the element protection layer may be, for example, a thermosetting resin such as epoxy resin, polyimide resin, or phenolic resin, or a thermoplastic resin such as polyethylene resin or polyamide resin. These resins may further contain a filler including silicon oxide, titanium oxide, or the like.
[0023] FIG. 4 is a schematic diagram showing a manufacturing process for the inductor 1. As shown in FIG. As shown in the figure, the manufacturing process for the inductor 1 includes a coil conductor molding step, a tablet molding step, a thermoforming and hardening step, a barrel polishing step, and an external electrode forming step.
[0024] The coil conductor molding process is a process for forming the coil conductor 20 from a conductive wire. In this process, the coil conductor 20 is formed into a shape having the above-mentioned winding portion 22 and a pair of lead-out portions 24 by winding the conductive wire in a manner called "alpha winding." Alpha winding refers to a state in which the conductive wire, which functions as a conductor, is wound in two stages in a spiral shape so that the lead-out portions 24 at the start and end of the winding are located on the outer periphery. The number of turns of the coil conductor 20 is not particularly limited.
[0025] The tablet molding process is a process for molding a preform called a tablet. The preform is formed by pressing the above-mentioned mixed powder, which is the material of the base body 2, into a solid form that is easy to handle. In this embodiment, two types of tablets are formed: a first tablet of an appropriate shape (e.g., E-shaped) having a groove into which the coil conductor 20 fits, and a second tablet of an appropriate shape (e.g., I-shaped or plate-shaped) that covers the groove of the first tablet.
[0026] In the thermoforming and curing process, the first tablet, the coil conductor, and the second tablet are set in a molding die, and while applying heat, pressure is applied in the overlapping direction of the first tablet and the second tablet, and they are cured to integrate the first tablet, the coil conductor, and the second tablet. This forms the element body 2 in which the coil conductor 20 is enclosed in the core 30.
[0027] The barrel polishing step is a step of barrel polishing this molded body, and by this step, the corners of the element body 2 are rounded.
[0028] The external electrode forming step is a step of forming the external electrodes 4 on the element body 2, and includes a laser irradiation step and an electrode layer forming step.
[0029] 5 is a schematic diagram showing the configuration of the LT cross section of the inductor 1. The LT cross section is a cut surface taken along a LT plane including the length direction DL and thickness direction DT of the core 30. The laser irradiation step is a step of modifying the surface of electrode formation regions 70 on the surface of element body 2, where external electrodes 4 are to be formed, by irradiating electrode formation regions 70 with laser light. After the laser irradiation, a cleaning process (eg, an etching process) may be performed to clean the surface of the electrode formation region 70.
[0030] The metal layer forming step is a step of forming the external electrode 4 by stacking various metal layers on the electrode formation region 70 whose surface has been modified by laser irradiation. Specifically, in this process, first, a conductive resin paste is applied to the entire surface of the electrode formation region 70 to form a base electrode 74, and then a nickel (Ni) layer 76 and a tin (Sn) layer 78 are laminated in this order on the surface of this base electrode 74 by plating growth to form the external electrode 4.
[0031] The conductive resin paste that is the material of the base electrode 74 is a mixed material in which conductive powder and resin are mixed, and in this embodiment, the conductive powder content (=conductive powder / (conductive powder+resin)) is 0.88. The conductive powder content is preferably 0.87 to 0.89.
[0032] In this embodiment, the conductive powder is silver powder, and includes first conductive particles and second conductive particles having different average particle sizes. In this embodiment, the average particle size of the first conductive particles is 5 μm, and it is preferable that the average particle size of the first conductive particles is 1 μm or more and 30 μm or less, and the average particle size of the second conductive particles is 80 nm, and it is preferable that the average particle size of the second conductive particles is 0.5 nm or more and 200 nm or less.
[0033] In this embodiment, the ratio of the average particle size of the first conductive particles to the second conductive particles (=average particle size of the second conductive particles / average particle size of the first conductive particles) is 0.2 to 0.11, and the compounding ratio (weight ratio) of the first conductive particles to the second conductive particles is 6: 4. It is preferable that the compounding ratio (weight ratio) of the first conductive particles to the second conductive particles is 3.5 or more for the second conductive particles. In addition, the content ratio of the first conductive particles to the resin (=first conductive particles / resin) is 0.528, preferably 0.522 or more and 0.534 or less, and the content ratio of the second conductive particles to the resin (second conductive particles / resin) is 0.352, preferably 0.348 or more and 0.356 or less.
[0034] In this embodiment, the resin is an acrylic thermosetting resin.
[0035] In the base electrode 74, the conductive powder contains first conductive particles and second conductive particles having different average particle sizes, and since the average particle size of the second conductive particles is smaller than that of the first conductive particles, the second conductive particles penetrate into the gaps between the first conductive particles. As a result, contact between the conductive particles in the conductive powder occurs not only between the first conductive particles and between the second conductive particles, but also between the first conductive particles and the second conductive particles, increasing the contact area between the conductive particles. This increase in contact area increases the number of current paths in the conductive powder, and therefore reduces the resistance value of the external electrode 4 including the base electrode 74.
[0036] Here, the element body 2 is designed so that the adhesive strength of the external electrodes 4 formed in the electrode formation regions 70 is improved by surface modification using laser irradiation of the electrode formation regions 70 in the external electrode formation step.
[0037] In detail, the base body 2 of this embodiment is molded from a mixed powder in which the proportion of metal magnetic powder (= weight of metal magnetic powder / (weight of metal magnetic powder + weight of resin)) is 97 wt% and the proportion of resin (= weight of resin / (weight of metal magnetic powder + weight of resin)) is 3.0 wt%, based on the total weight of the metal magnetic powder and resin. Furthermore, in the base body 2 after laser irradiation, the electrode formation region 70, which is the surface with which the external electrode 4 comes into contact, has a metal area ratio of 70%, while the metal area ratio of areas other than the electrode formation region 70 is 38%. In this case, the electrode formation region 70 has a surface roughness Sa of 10 μm, whereas the surface of the body 2 other than the electrode formation region 70 has a surface roughness Sa of 1.8 μm, making the electrode formation region 70 more than five times rougher than the other areas. The metal area ratio is the ratio of the area of the metal magnetic powder to the total area of the metal magnetic powder and the resin (=area of the metal magnetic powder / (total area of the resin and the metal magnetic powder)).
[0038] Table 1 shows the relationship between surface roughness Sa and the adhesion strength of the external electrode 4 (unit: kg / mm 2 ) and Fig. 6 is a graph of the experimental results in Table 1. The experimental results in Table 1 were obtained by varying the irradiation intensity (energy) of the laser light irradiated onto the electrode formation region 70 to change the surface roughness Sa, and measuring the adhesion strength of the external electrodes 4 formed on the electrode formation region 70. The adhesion strength was measured using a bond tester.
[0039] [Table 1]
[0040] In practice, the threshold Ath of adhesion strength that does not cause peeling problems is 0.4 (kg / mm 2 ), it can be seen that, as shown in Table 1 and FIG. 6, if the surface roughness Sa is about 4.8 (μm) or more, an adhesion strength equal to or greater than the threshold Ath is obtained. As described above, in the inductor 1 of this embodiment, the surface roughness Sa of the electrode formation region 70 is 10 μm, so it is understood that sufficient bonding strength is obtained.
[0041] Table 2 shows the results of an experiment investigating the relationship between the metal area ratio and the surface roughness Sa, and FIG. 7 is a graph of the experimental results of Table 2. In Table 2, the area energy (unit: mJ / mm 2 ) is the laser energy per unit area. Moreover, the experimental results in Table 2 are the average values of the metal area ratios measured for three element bodies 2, and the metal area ratios for each element body 2 were measured as follows. First, a photographing point is set within the surface of the electrode formation region 70 for each of the end faces 14, the top face 12, and the mounting face 10 of the element body 2. The photographing points are the intersections of the four diagonal corners of the electrode formation region 70 on each face to be photographed. Next, each photographing point is photographed at a magnification of 500 times using the reflected electron mode of a scanning electron microscope, and the photographed image at each photographing point is binarized. Next, the metal magnetic powder is identified within each photographed image after binarization, and the proportion of the area occupied by the metal magnetic powder in each photographed image is calculated as the metal area ratio. The average value of the metal area ratios of each photographed image is then determined as the metal area ratio of the element body 2. In addition, the metal area ratio of the surfaces of the element body 2 other than the electrode formation region 70 was measured for each of the top surface 12 and mounting surface 10 of the element body 2, with the intersections diagonally connecting the four corners of each surface to be photographed being used as the photographing points, in the same manner as the measurement procedure described above for the metal area ratio of the electrode formation region 70.
[0042] [Table 2]
[0043] As shown in Table 2 and Fig. 7, it can be seen that the surface roughness Sa becomes rougher as the metal area ratio increases. It can be seen that an adhesion strength equal to or greater than the above-mentioned threshold Ath can be obtained if the surface roughness Sa is 4.8 (μm) (Bth in Fig. 6) or more as shown in Fig. 6, and that such a surface roughness Sa can be obtained if the metal area ratio is about 65% or more (Cth in Fig. 7) as shown in Fig. 7.
[0044] FIG. 8 shows a micrograph of a cross section of the portion of the external electrode 4 of the inductor 1 together with a micrograph of the surface of the electrode formation region 70. In FIG. As shown in the figure, a large number of magnetic particles 80 (the above-mentioned first magnetic particles and second magnetic particles) are present in the electrode formation region 70 (surface) of the element body 2, and by irradiating the electrode formation region 70 with a laser, the resin on the surface is removed and adjacent magnetic particles 80 are fused together. The fusion of the magnetic particles 80 in the electrode formation region 70 becomes more pronounced as the laser irradiation intensity increases, which increases the metal area ratio.
[0045] 7 and 8, it has been found that if the laser irradiation intensity is too strong, grain shedding occurs in the electrode formation region 70, causing unevenness on the surface of the external electrode 4 formed there. Specifically, when the metal area ratio is 75% (Cmax in FIG. 7) or less, unevenness in the external electrode 4 due to grain shedding is not observed, but when the metal area ratio is 78% or more, unevenness in the external electrode 4 is observed. Therefore, in order to prevent the occurrence of unevenness on the surface of the external electrode 4, it can be said that the metal area ratio is preferably 75% or less.
[0046] From the above, it can be seen that when the metal area ratio of the electrode formation region 70 is 65% or more and 75% or less, the adhesive strength of the external electrode 4 is sufficient and the occurrence of unevenness on the surface of the external electrode 4 can be suppressed.
[0047] The inventors have confirmed through experiments that, in the element 2, when the proportion of metal magnetic powder (= weight of metal magnetic powder / (weight of metal magnetic powder + weight of resin)) is 96.7 wt% or more and 97.4 wt% or less, and the proportion of resin (= weight of resin / (weight of metal magnetic powder + weight of resin)) is 2.6 or more and 3.3 wt% or less, based on the total weight of the metal magnetic powder and resin, the above-mentioned relationship between the metal area ratio and the bonding strength and the occurrence of unevenness on the surface of the external electrode 4 can be obtained.
[0048] According to this embodiment, the following effects are obtained.
[0049] The inductor 1 of this embodiment has an element body 2 in which a coil conductor 20 is embedded in a core 30 containing metal magnetic powder and resin, and an external electrode 4 formed in an electrode formation region 70 on the surface of the element body 2. Based on the total weight of the metal magnetic powder and resin, the element body 2 has a metal magnetic powder ratio of 96.7 wt% to 97.4 wt% and a resin ratio of 2.6 to 3.3 wt%, and the electrode formation region 70 of the element body 2 has a metal area ratio of 65% to 75%, which is the ratio of the area of metal to the total area of metal and resin resulting from the metal magnetic powder. This ensures that the external electrodes 4 are secured to each other with sufficient strength, and also prevents the occurrence of irregularities on the surfaces of the external electrodes 4.
[0050] In this embodiment, the external electrode 4 comprises a base electrode 74 formed in the electrode formation region 70 of the base body 2 using a conductive resin paste containing first conductive particles and second conductive particles having different average particle sizes, and a resin, and a plating layer (nickel layer 76 and tin layer 78) formed on the surface of this base electrode 74. By containing the first conductive particles and the second conductive particles having different average particle sizes, the current flow path and area in the base electrode 74 are increased, and the resistance value of the external electrode 4 including the base electrode 74 can be reduced.
[0051] [Second embodiment] Fig. 9 is a schematic diagram showing the configuration of an LT cross section of an inductor 1 according to a second embodiment of the present invention. Fig. 10 is a diagram showing the correspondence between the cross-sectional configuration of a portion including an extension portion 90 of an external electrode 4 and the planar configuration of the inductor 1 as viewed from a mounting surface 10.
[0052] The inventors have found through experiments similar to those relating to Figures 6 and 7 of the first embodiment that when the metal area ratio of the electrode formation region 70 of the element body 2 is 65% or more and 75% or less, not only the adhesion strength of the conductive resin paste but also the adhesion strength of the nickel layer 76 is improved to the same extent as that of the conductive resin paste, and further, the occurrence of unevenness on the surface of the external electrode 4 is suppressed. More specifically, when the metal area ratio of the electrode formation region 70 is 65% or more, the electrical conductivity of the electrode formation region 70 increases, making it easier for plating to grow in the electrode formation region 70 and also increasing the contact area between the metal magnetic powder and the nickel layer 76, improving the bonding strength. On the other hand, when the metal area ratio of the electrode formation region 70 exceeds 75%, the laser irradiation intensity becomes too strong, causing the metal magnetic powder to fall off, making it difficult for plating to grow and causing unevenness to occur on the surface of the external electrode 4.
[0053] In this way, the adhesive strength of the nickel layer 76 is increased in accordance with the metal area ratio of the electrode formation region 70 . Therefore, in an external electrode 4 having a base electrode 74 made of a conductive resin paste, a nickel layer 86 (plating layer) on the base electrode 74, and a tin layer 78 on the nickel layer 76, the base electrode 74 being formed in an electrode formation region 70 having a metal area ratio of 65% to 75%, the adhesive strength of the external electrode 4 can be increased more than that of the first embodiment by doing the following: That is, as shown in Figures 9 and 10, by providing an extension 90 that directly touches the surface of the electrode formation region 70 on the nickel layer 76 (plating layer) of the external electrode 4, in addition to the adhesive strength between the base electrode 74 and the electrode formation region 70, the adhesive strength of the external electrode 4 can be increased by the extension 90, making it more difficult for the external electrode 4 to peel off. As shown in FIG. 9, each of the pair of external electrodes 4 has an extension portion 90 on each of the mounting surface 10 and the top surface 12, and as shown in FIG. 10, each extension portion 90 extends between a pair of side surfaces 16 of the inductor 1, thereby increasing the bonding strength compared to when the extension portion 90 is not present. In the external electrode 4 of this embodiment, the metal area ratio of the surface of the electrode formation region 70 with which the extension portion 90 contacts is higher than the metal area ratio of the surface of the element body 2 other than the electrode formation region 70, and even if it is less than 65%, the adhesion strength can be stronger than that of the first example due to the adhesion strength of the base electrode 74 and the adhesion strength of the extension portion 90. Furthermore, by setting the metal area ratio of the surface of the electrode formation region 70 with which the extension portion 90 contacts to be 65% or more and 75% or less, the conductivity of the electrode formation region 70 is increased compared to when the metal area ratio is less than 65%, making it easier for plating to grow in the electrode formation region 70 and also increasing the contact area between the metal magnetic powder and the nickel layer 76, thereby increasing the adhesion strength of the extension portion 90.
[0054] [Third embodiment] FIG. 11 is a schematic diagram showing the configuration of an LT cross section of an inductor 1 according to a third embodiment of the present invention. As described in the second embodiment, when the metal area ratio of the electrode formation region 70 of the element body 2 is 65% or more and 75% or less, the adhesion strength of the nickel layer 76 to the electrode formation region 70 is improved, and the occurrence of unevenness on the surface of the external electrode 4 is suppressed. 11 , it is also possible to configure an external electrode 4 in which a nickel layer 76 and a tin layer 78, which are plating layers, are formed directly on the electrode formation region 70 of the element body 2, without forming a base electrode 74 in the electrode formation region 70. In this case, in the external electrode 4, the plating layer is directly connected to the lead-out portion 24 of the coil conductor 20. The plating layers may be formed in the order of copper (Cu) layer, nickel layer 76, and tin layer 78, and the external electrodes 4 with sufficient adhesive strength can be obtained with such plating layers as well.
[0055] Each of the above-described embodiments is merely an example of one aspect of the present invention, and any modification or application is possible without departing from the spirit of the present invention.
[0056] In each of the above-described embodiments, the shape of the external electrode 4 is not limited to a five-surface electrode, and may be, for example, an L-shaped electrode or a bottom electrode.
[0057] In the above-described embodiments, unless otherwise specified, the horizontal, vertical, and other directions, various numerical values, shapes, and materials include a range in which the same action and effect as those directions, numerical values, shapes, and materials are achieved (a so-called equivalent range). [Explanation of symbols]
[0058] 1 Inductor 2 Base 4 External electrode 20 Coil conductor 30 cores 70 Electrode formation area (surface in contact with external electrodes) 74 Base electrode 76 Nickel layer (plating layer) 78 Tin layer 90 Extension part
Claims
1. An inductor having an element body having a coil conductor embedded in a core containing metal magnetic powder and resin, the element body having a top surface, a mounting surface, end surfaces, and side surfaces, and external electrodes formed on surfaces of the element body, The element body is Based on the total weight of the metal magnetic powder and the resin, the ratio of the metal magnetic powder is 96.7 wt % or more and 97.4 wt % or less, and the ratio of the resin is 2.6 wt % or more and 3.3 wt % or less, the external electrode comprises: a base electrode formed on a surface of the element body by a conductive resin containing first conductive particles and second conductive particles having average particle diameters different from each other, and a resin; and a plating layer formed on the surface of the base electrode; a metal area ratio, which is a ratio of an area of the metal magnetic powder to a total area of the metal magnetic powder and the resin, of a surface of the element body with which the base electrode is in contact is 65% or more and 75% or less; the plating layer has an extension portion that extends from the base electrode to a surface of the element body on at least the mounting surface of the element body, the metal area ratio of a region on the surface of the element body that is in contact with the extension portion of the plating layer is higher than the metal area ratio of a region other than a region that is in contact with the external electrode, a surface of the element body with which the extending portion of the plating layer is in contact has a metal area ratio of 65% or more and 75% or less and a surface roughness of 5.2 μm or more and 14.5 μm or less; Inductor.
2. the plating layer has the extension portion on the top surface and the mounting surface of the element body, the metal area ratio of a region of the top surface and the mounting surface of the element body where the extension portion of the plating layer contacts is higher than the metal area ratio of a region other than a region where the external electrode contacts, a surface of the element body with which the extending portion of the plating layer is in contact has a metal area ratio of 65% or more and 75% or less and a surface roughness of 5.2 μm or more and 14.5 μm or less; 2. The inductor of claim 1.
Citation Information
Patent Citations
Chip-type electronic component
JP2003297646A
Coil device
JP2016146431A
Conductive paste for terminal electrode for laminated ceramic electronic component
JP2020088353A